Temporal and spatial investments in the protected area network of a megadiverse country - Rodolfo Cabral; Daniel Brito (Zoologia (Curitiba), 2013)
Protected area networks are the cornerstone strategy for biodiversity conservation worldwide. They are efficient even in the face of human pressures. Brazil is a megadiverse country and for this reason it should not be left out of discussions on biodiversity conservation. Here we present a temporal and spatial analysis of the historical national investments in the country's protected area network. We compare this investment in the light of international biodiversity agreements (e.g., CBD), and evaluate trends and biases in the establishment of protected areas. We obtained the following data from a database maintained by the Brazilian government: the number of protected areas, the dates when they were established, their size and category (strict protection or sustainable use). Our results show that Brazil does not meet the recommended international levels of protection, that its network coverage favors a few of its biomes only, and that the temporal flow of investments has varied greatly. Even though there is a tendency for an increase in the establishment of protected areas, there has been a noteworthy change in the categories more recent protected areas are inserted. Until the 1980's the network was comprised mostly of strict protection sites, whereas the newly created sites are mostly intended for sustainable use. This reflects a serious philosophical and practical change in the role of the national protected area network, and may affect its objectives in preserving the biodiversity of a country that plays a key role in the global biodiversity conservation scenario.